An isothermal amplification-based point-of-care diagnostic platform for the detection of Mycobacterium tuberculosis: A proof-of-concept study - Shanmugakani, Rathina Kumar (Curr Res Biotechnol, 2021)
The timely diagnosis of active tuberculosis disease (TB) is crucial to interrupt the transmission and combat the spread of Mycobacterium tuberculosis (Mtb), the causative agent for TB. Here, we demonstrate the development of a specimen-direct rapid diagnostic method for TB which consists of an isothermal amplification device, Tiny Isothermal Nucleic acid quantification sYstem (TINY), coupled with helicase-dependent amplification (HDA). HDA, an isothermal amplification technique is established over TINY using pUCIDT-AMP vector carrying IS6110, the target DNA sequence for Mtb. The limit of detection of this technique for detecting the IS6110 within a threshold time of 50 min is 2.5 × 10(5) copies of IS6110. HDA in TINY for TB detection was evaluated using three IS6110-positive Mtb strains – H37Rv, CDC 1551, and Erdman wild-type and one IS6110-negative Mycobacterium avium. For spiked oral swabs, HDA in TINY detects IS6110 without any non-specificity in relatively short turnaround time (<1.5 h), highlighting its potential utility as a specimen-direct point-of-care diagnostic for TB. TINY does not require an uninterrupted power supply and its lightweight and small footprint offers portability and easier operation in clinical settings with poor infrastructure. Overall, HDA in TINY could serve as an efficient rapid, and portable platform for the qualitative detection of TB at the point-of-care.